Different macrophages equally induce EMT in endometria of adenomyosis and normal. Issue 1 (July 2017) - An, Min; Li, Dong; Yuan, Ming; Li, Qiuju; Zhang, Lu; Wang, Guoyun
Abstract : Endometrial cells and microenvironment are two important factors in the pathogenesis of adenomyosis. Our previous study demonstrated that macrophages can induce eutopic epithelial cells of adenomyosis to suffer from epithelial–mesenchymal transition (EMT). The aim of this study is to detect whether macrophages interacting with epithelial cells equally induce the EMT process in normal and eutopic endometria of healthy and adenomyotic patients; and whether macrophages parallelly polarize to M2. We investigated the expression levels of epithelial cadherin (E-cadherin), neural cadherin (N-cadherin), cytokeratin7 (CK7), vimentin, transforming growth factor-β1 (TGFB1), SMAD3 and pSMAD3 using immunohistochemistry and western blot, and then estimated the genetic levels of CD163, IL10 and MMP12 using real-time quantitative polymerase chain reaction (RT-PCR) in macrophages. Eutopic and normal endometrial tissues were obtained from 20 patients with adenomyosis and 11 control patients without adenomyosis, respectively. The immunohistochemical analysis shows distinct EMT in eutopic endometria in secretory phase; the expression levels of TGFB1, SMAD3 and pSMAD3 that indicate signal pathway of EMT were also higher in secretory phase. Macrophages can induce EMT process in primary endometrial epithelial cells derived from normal and eutopic endometria. After co-culturing, THP-1-derived macrophages polarized to M2. Compared with the eutopic endometrium group, further polarization to M2 was observed in the normal endometrium group. These results indicate that adenomyosis may be promoted by the pathologic EMT of epithelial cells, which is induced by macrophages that incapably polarize to M2.